Effects of flavopiridol on critical regulation pathways of CD133high/CD44high lung cancer stem cells. Issue 43 (October 2016) - Bozok Cetintas, Vildan; Acikgoz, Eda; Yigitturk, Gurkan; Demir, Kenan; Oktem, Gulperi; Tezcanli Kaymaz, Burçin; Oltulu, Fatih; Aktug, Huseyin
Abstract: Background: Flavopiridol a semisynthetic flavone that inhibits cyclin-dependent kinases (CDKs) and has growth-inhibitory activity and induces a blockade of cell-cycle progression at G1-phase and apoptosis in numerous human tumor cell lines and is currently under investigation in phase II clinical trials. Cancer stem cells (CSCs) are comprised of subpopulation of cells in tumors that have been proposed to be responsible for recurrence and resistance to chemotherapy. The aim of the present study was to investigate the effects of flavopiridol in cancer stem cell cytoskeleton, cell adhesion, and epithelial to mesenchymal transition in CSCs. Methods: The cells were treated with flavopiridol to determine the inhibitory effect. Cell viability and proliferation were determined by using the WST-1 assay. Caspase activity and immunofluorescence analyses were performed for the evaluation of apoptosis, cell cytoskeleton, and epithelial-mesenchymal transition (EMT) markers. The effects of flavopiridol on the cell cycle were also evaluated. Flow cytometric analysis was used to detect the percentages of CSCs subpopulation. We analyzed the gene expression patterns to predict cell cycle and cell cytoskeleton in CSCs by RT-PCR. Results: Flavopiridol-induced cytotoxicity and apoptosis at the IC50 dose, resulting in a significant increase expression of caspases activity. Cell cycle analyses revealed that flavopiridol induces G1 phase cell cycle arrest. Flavopiridol significantly decreased the mRNA expressions of the genes that regulate the cell cytoskeleton and cell cycle components and cell motility in CSCs. Conclusion: Our results suggest that Flavopiridol has activity against lung CSCs and may be effective chemotherapeutic molecule for lung cancer treatment.